A clinicopathological analysis of forkhead box A1 (FOXA1) and estrogen receptor alpha expression in extramammary Paget’s disease - Chiho Sumitomo; Yohei Iwata; Masaru Arima; Kazumitsu Sugiura (Fujita Medical Journal, 2023)
Objectives: Extramammary Paget’s disease (EMPD) is a neoplastic skin disease of unknown etiology. EMPD is frequently associated with forkhead box A1 (FOXA1) expression, which correlates with the expression of estrogen receptor alpha (ER). FOXA1 regulates the transcriptional activity of ER and may function cooperatively in the tumorigenesis of breast cancer.